2022
DOI: 10.3390/polym14122353
|View full text |Cite
|
Sign up to set email alerts
|

Development of Aloe Vera-Green Banana Saba-Curcumin Composite Film for Colorimetric Detection of Ferrum (II)

Abstract: This study was performed to develop and characterize a bio-film composed of Aloe vera (Aloe barbadensis), green banana Saba (Musa acuminata x balbisiana), and curcumin for the detection of Fe2+ ions. Cross-linking interaction between banana starch-aloe vera gel and banana starch-curcumin enhanced l the sensing performance of the composite film towards divalent metal ions of Fe2+. The morphological structure of the Aloe vera-banana starch-curcumin composite revealed a smooth and compact surface without cracks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…A red-brown colour was also observed for Fe 3+ at pH 2 [92], although it was claimed to be selective against Ni, Cu, K, Mn, Cr, Mg, Zn, Na, Ca, Ba, Cd and Co ions, and was found to be the most sensitive for Fe 3+ [30,59,91,92]. Fe 2+ detection was also performed using a biofilm composed of mixed curcumin, banana (Musa acuminata x balbisiana) and aloe vera (Aloe barbadensis); a greenish-brown colour was observed and confirmed by UV-Vis spectroscopy, with a wavelength shift from 426 nm to 410 nm [88]. The main challenge of using curcumin as a colorimetric indicator for metal detection is its naturally pH-dependent property, which may lead to false positives, especially in alkaline conditions, although some studies reported that the methods are selective for certain metals.…”
Section: Curcuminoidsmentioning
confidence: 86%
See 1 more Smart Citation
“…A red-brown colour was also observed for Fe 3+ at pH 2 [92], although it was claimed to be selective against Ni, Cu, K, Mn, Cr, Mg, Zn, Na, Ca, Ba, Cd and Co ions, and was found to be the most sensitive for Fe 3+ [30,59,91,92]. Fe 2+ detection was also performed using a biofilm composed of mixed curcumin, banana (Musa acuminata x balbisiana) and aloe vera (Aloe barbadensis); a greenish-brown colour was observed and confirmed by UV-Vis spectroscopy, with a wavelength shift from 426 nm to 410 nm [88]. The main challenge of using curcumin as a colorimetric indicator for metal detection is its naturally pH-dependent property, which may lead to false positives, especially in alkaline conditions, although some studies reported that the methods are selective for certain metals.…”
Section: Curcuminoidsmentioning
confidence: 86%
“…Metal detection was then developed using synthesised curcumin-based materials, such as nanofibers, nanoparticle films, cryogels, biofilms, and zein membranes, as summarised in Table 2. Fabricated modification is one of the alternatives to improve the bioavailability, solubility, and stability of curcumin; it also tends to improve the chelating ability, sensitivity, and selectivity of curcumin-based sensors [88]. In terms of portability, nanofiber-type materials are highly portable as they are ready to use in fabricated form, easy to handle, simple and stable, and suitable for rapid colorimetric detection with visual observation [89].…”
Section: Curcuminoidsmentioning
confidence: 99%
“…The presence of Pb 2+ caused the color to change from orange to red, with detection limits of 9 µM and 0.9 µM through observation with the naked eye and image processing, respectively. Vonnie et al [ 42 ] investigated the activity of a biofilm containing Aloe vera, green banana Saba, and curcumin in detecting Fe 2+ ions. Using colorimetric analysis, good linearity (R 2 = 0.9845) was found for Fe 2+ ions concentrations of 0 to 100 ppm, with limits of detection and quantification found to be 27.84 ppm and 92.81 ppm, respectively.…”
Section: Application Of Natural-derivedmentioning
confidence: 99%
“…35 The diketone group in curcumin can also be functionalized by interacting with polymers bearing boronic acids 36,37 or complexation with metal ions. 38,39 Because the carrier polymers in drug-polymer conjugates are usually pharmaceutically inactive and only serve as a scaffold, drug loading is limited. 40,41 Higher drug loading can be achieved by directly incorporating curcumin into the polymer's chemical structure, where such poly(pro-drugs) act both as the carrier matrix material and a depot of the drug itself.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another strategy to enhance the solubility and long-term stability of curcumin is to conjugate the reactive phenol groups to the side chains of polyethylene glycol, , hyaluronic acid, sodium alginate, or xylan . The diketone group in curcumin can also be functionalized by interacting with polymers bearing boronic acids , or complexation with metal ions. , Because the carrier polymers in drug-polymer conjugates are usually pharmaceutically inactive and only serve as a scaffold, drug loading is limited. , Higher drug loading can be achieved by directly incorporating curcumin into the polymer’s chemical structure, where such poly­(pro-drugs) act both as the carrier matrix material and a depot of the drug itself . Curcumin-containing polyacetals, , polyoxalates, polycarbonates, , polyurethane, and polyesters , have been reported, and the release of curcumin from these materials were either rapid (<30 h) or sustained (2–80 days), ,,, depending on the stability of the linker chemistry used to enchain the drug molecules.…”
Section: Introductionmentioning
confidence: 99%